Non-stick cookware and method of making the same
By forming a composite metal oxide layer with amorphous structure and concave and convex structure on the cookware and filling it with low surface energy materials, the existing non-stick cookware materials are solved in terms of initial and long-lasting non-stick properties, achieving more durable non-stick properties.
Patent Information
- Application Number
- CN202510080924.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-04
AI Technical Summary
The existing non-stick cookware materials are difficult to take into account both initial non-stick and long-lasting non-stick, and are easily damaged by spatulas, aging or decomposing at high temperatures.
A composite metal oxide layer with an amorphous structure is adopted. The surface of the composite metal oxide layer has an uneven structure, and the depressions are filled with low surface energy materials, including iron and titanium elements of different valence states.
It achieves the consideration of the initial non-stickness and long-lasting non-stickness of the cookware, has good hardness and chemical stability, and extends the service life of non-stick properties.
Smart Images

Figure CN119745244A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of non-stick cookware, and more specifically, to a non-stick cookware and a manufacturing method thereof. Background Art
[0002] In the art, fluorine coating is a common non-stick coating. However, the non-stick coating made of fluorine coating has excellent initial non-stick properties, but it is easily damaged by a spatula and is easily aged or decomposed due to high temperature during use. These problems have seriously affected the service life of the coating formed by fluorine coating, resulting in the coating having poor long-term non-stick properties.
[0003] Therefore, developing cookware with both initial non-stick properties and lasting non-stick properties remains a problem that needs to be solved. Summary of the invention
[0004] Therefore, the object of the present application is to provide a non-stick cookware and a method for manufacturing the same, so as to solve the problem that the existing cookware formed by non-stick materials cannot have both initial non-stick properties and lasting non-stick properties.
[0005] According to a first aspect of the present application, a non-stick cookware is provided, wherein the non-stick cookware comprises a substrate and a composite metal oxide layer having an amorphous structure disposed on the substrate, wherein the surface of the composite metal oxide layer has a concave-convex structure, and low surface energy materials are formed at the recesses of the concave-convex structure, wherein the metal elements in the composite metal oxide layer comprise iron elements of different valence states and titanium elements of different valence states.
[0006] According to the non-stick cookware provided in the embodiment of the present application, the composite metal oxide layer has a certain initial non-stick property, does not age with the extension of the use time, has good hardness and chemical stability, and can at least protect the low surface energy material located in the depression. Therefore, the non-stick cookware can have a more durable and long-lasting non-stick property.
[0007] In some embodiments, the iron elements of different valence states include +2 and +3, and the titanium elements of different valence states include at least two of +2, +3 and +4.
[0008] In these embodiments, the above-mentioned iron elements and titanium elements in different valence states are arranged in the crystal lattice in a different manner, which can make the non-stick material have an amorphous structure and facilitate the manufacturing and formation of the composite metal oxide and better stability.
[0009] In some embodiments, carbonized products of a binder are also dispersed in the composite metal oxide layer. On the one hand, the presence of the carbonized products of the binder can facilitate the connection of the various particles of the matrix and ensure the internal bonding strength of the various particles of the non-stick material. On the other hand, using the carbonized products of the binder as a connecting bridge between the various particles of the matrix can make the composite metal oxide layer as a whole present higher hardness and stability.
[0010] In some embodiments, the weight ratio of the carbonized product of the binder to the composite metal oxide is (0.4-3.5):(96.5-99.6). The carbonized product of the binder and the composite metal oxide have a suitable weight ratio, so that excessive carbonized product of the binder can be prevented from affecting the overall strength of the non-stick material.
[0011] In some embodiments, the porosity of the composite metal oxide layer is 5% to 30%, and the pore size is 500 nanometers to 4 micrometers.
[0012] In these embodiments, the above pores can easily connect more low surface energy materials, thereby enhancing the non-stick performance of the non-stick cookware.
[0013] In some embodiments, the composite metal oxide layer is formed of a composite metal oxide, which is a material in which the volume percentage of the amorphous phase is in the range of 30%-70%. Correspondingly, the volume percentage of the amorphous phase of the composite metal oxide layer is 30%-70%. Such a composite metal oxide with a high volume percentage of the amorphous phase has low surface energy and higher wear resistance and stability, and thus can form a composite metal oxide layer with better non-stick properties and wear resistance.
[0014] In some embodiments, the low surface energy material includes at least one of silane materials, oil molecules, fluorine coatings and ceramic coatings. Having a lower surface energy than the composite metal oxide layer can further improve the non-stick performance of non-stick cookware, especially can optimize the initial non-stick performance.
[0015] According to a first aspect of the present application, a method for manufacturing non-stick cookware is provided, wherein the method for manufacturing non-stick cookware comprises: forming a mixed slurry comprising a binder and a base material, wherein the base material comprises titanium oxide and ferrosoferric oxide; spray-drying the mixed slurry to obtain non-stick particles; sintering the non-stick particles to slightly melt the base material in the non-stick particles, thereby obtaining a composite metal oxide comprising iron elements of different valence states and titanium elements of different valence states and having an amorphous structure; spraying the composite metal oxide on a substrate to form a composite metal oxide layer having a concave-convex structure on the substrate; and forming a low surface energy material at least at the concave portion of the concave-convex structure, thereby manufacturing the non-stick cookware.
[0016] In some embodiments, the weight ratio of the base material to the binder is (52-70): (30-48). In the mixed slurry, the weight ratio of the binder is equivalent to that of the base material. Such a large amount of binder will volatilize in the subsequent steps, so that it is easy to form composite metal oxide particles with a three-dimensional macroporous structure while ensuring the overall strength, so that the composite metal oxide layer formed by this composite metal oxide can retain the three-dimensional macroporous structure of the composite metal oxide, thereby ensuring the formation of a three-dimensional pore structure of the composite metal oxide layer. And / or, the weight ratio of titanium oxide to ferroferric oxide is (13-39): (13-39). Within this ratio range, titanium oxide and ferroferric oxide can easily form a composite metal oxide through chemical reaction at a high temperature of subsequent sintering, and can minimize the impact of the unreacted part on the overall composite metal oxide. In addition, within this ratio range, the synergistic effect of titanium oxide and ferroferric oxide can be beneficial to increase the degree of amorphization of the composite metal oxide.
[0017] In some embodiments, the binder includes an alcohol binder and / or a cellulose binder, specifically, the cellulose binder includes at least one of a hydroxymethyl cellulose binder, a hydroxyethyl cellulose binder, and a hydroxypropyl cellulose binder, and the alcohol binder includes at least one of a polyvinyl alcohol binder, a polypropylene alcohol binder, and a higher alcohol binder containing more than six carbon atoms. The above-mentioned binder can facilitate the connection of the individual particles of the base material, thereby facilitating the formation of the expected composite metal oxide.
[0018] In some embodiments, the sintering step includes heating the non-stick particles to 500°C-650°C at a heating rate of 15°C / min-20°C / min, keeping the temperature for 6h-8h, and then heating the non-stick particles to 1200°C-1250°C at a heating rate of 55°C / min-100°C / min, and keeping the temperature for 12h-24h. Under this parameter, the base material in the non-stick particles can be slightly melted to form the expected composite metal oxide.
[0019] In some embodiments, the particle size of the base material is 0.05 microns to 5 microns. When the base material is within the range of 0.05 microns to 5 microns, it is easier to form the composite metal oxide having an amorphous structure and a three-dimensional macroporous structure, and the porosity of the composite metal oxide layer (composite metal oxide layer) formed can be controlled to easily meet the requirements of locking oils. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or other features and aspects of the inventive concept will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings.
[0021] Figure 1 is a scanning electron microscope image of a non-stick particle provided according to an embodiment of the present application;
[0022] Figure 2 is a scanning electron microscope image of a composite metal oxide provided according to an embodiment of the present application;
[0023] Figure 3 is an XRD spectrum of a composite metal oxide provided according to an embodiment of the present application;
[0024] Figure 4 is a schematic diagram of the cross-sectional structure of the non-stick cookware provided in an embodiment of the present application after being cut along the thickness direction;
[0025] Figure 5 yes Figure 4 Schematic diagram of the enlarged structure at I in the middle.
[0026] Explanation of symbols:
[0027] 100. non-stick cookware; 110. substrate; 120. composite metal oxide layer; 130. transition layer; 150. low surface energy material. DETAILED DESCRIPTION
[0028] The exemplary embodiments of the inventive concept will be described in more detail below. Although the exemplary embodiments of the inventive concept are described below, it should be understood that the inventive concept can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to fully convey the scope of the inventive concept to those skilled in the art.
[0029] In this field, fluorine coating is a common non-stick material. However, the non-stick layer made of fluorine coating has excellent initial non-stick properties, but it is easily damaged by a spatula and is easily aged or decomposed due to high temperature during use. These problems have seriously affected the service life of the coating formed by fluorine coating, resulting in the general long-term non-stick properties of the coating formed by it. In addition, perfluoroalkyl and polyfluoroalkyl compounds (PFAS) are indispensable raw materials for synthesizing fluorine coatings. As the industry's control over perfluoroalkyl and polyfluoroalkyl compounds (PFAS) becomes increasingly strict, it is an inevitable trend for fluorine coatings to withdraw from the stage of non-stick cookware. This also means that the materials that can be used for pot coatings are gradually decreasing, so the development of new non-stick materials is still in urgent need in the field of pot manufacturing.
[0030] At present, no material with lower surface energy than fluorine coating has been found, but the demand for non-stick in the cookware industry always exists, and ceramic coating is expected to replace fluorine coating. Ceramic coating is a liquid coating with oil molecules as the main non-stick component. Although the initial non-stick property of the coating formed by it is close to that of fluorine coating, as high-temperature cooking proceeds, the oil molecules will be continuously consumed by the high temperature and quickly lose the non-stick effect. Therefore, the long-lasting non-stick property of ceramic coating cannot meet the demand for non-stick in cookware.
[0031] With the development of the non-stick industry, solid spray materials based on metals (e.g., iron, stainless steel, low carbon steel, high carbon steel, cast iron, and copper, etc.) or ceramics (e.g., titanium oxide, titanium nitride, titanium carbide, ferroferric oxide, ferrous oxide, ferrous oxide, aluminum oxide, chromium oxide, and nickel oxide, etc.) have emerged, which can form a non-stick layer, namely the so-called "coating-free non-stick technology". The coating-free here is only to indicate that it does not use organic coatings such as fluorine coatings or ceramic coatings. Although the coating formed by the above-mentioned spraying materials is wear-resistant, the cookware with the coating only has the effect of cooking without sticking in the presence of oil, and its initial non-stickiness is poor, and it usually needs to be modified with materials with good non-stickiness, such as using polysiloxanes and fluorinated materials to modify it, in order to meet the initial non-stickiness required by the national standard. In addition, the non-stickiness of such materials decreases rapidly after wear, and the residual polysiloxane will have a counter-effect on the non-stickiness, and the non-stickiness is worse than before the modification.
[0032] As can be seen from the above, existing non-stick materials are difficult to achieve both initial non-stick and lasting non-stick properties. Therefore, developing new non-stick materials with both initial non-stick and lasting non-stick properties plays an extremely important role in the field of cookware manufacturing.
[0033] According to a first aspect of the present application, a non-stick material for cookware or cupware is provided, wherein the non-stick material comprises composite metal oxide particles having an amorphous structure, wherein the metal elements in the composite metal oxide comprise iron elements of different valence states and titanium elements of different valence states.
[0034] In the present application, the composite metal oxide refers to a compound containing two or more metals and oxygen. As an example, the composite metal oxide is a multinary metal oxide including at least iron and titanium, and the multinary metal oxide has an amorphous structure, which means that its atomic or molecular arrangement has no long-range order. The amorphous structure gives the non-stick material some good properties, such as high hardness, high wear resistance and good thermal stability.
[0035] According to the composite metal oxide provided by the embodiment of the present application, the arrangement of iron and titanium elements of different valence states in the crystal lattice is different, so that the composite metal oxide has an amorphous structure, and the composite metal oxide itself has a low surface energy and has a certain initial non-stick property. In addition, the composite metal oxide layer formed by the composite metal oxide will not age with the extension of the use time, and has good physical and chemical stability. Therefore, it can have a more durable and long-lasting non-stick property.
[0036] In some embodiments, the iron elements of different valence states include +2 and +3, and the titanium elements of different valence states include at least two of +2, +3 and +4.
[0037] In these embodiments, the above-mentioned iron elements and titanium elements in different valence states are arranged in the crystal lattice in a different manner, which can make the composite metal oxide have an amorphous structure and is beneficial to the manufacturing, formation and stability of the composite metal oxide.
[0038] According to the present application, the composite metal oxide includes a composite metal oxide having an amorphous structure. In some embodiments, the composite metal oxide is composed of FeTiO3, Fe2TiO5 and Fe3Ti3O 10 For the iron-titanium oxide, the general formula is Fe (a+b) Ti (c+d) O e To illustrate, as some examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +2, d is the number of titanium atoms with a valence of +4, and e is the number of oxygen atoms with a valence of +2, where 2a+3b+2c+4d=2e. As other examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +2, d is the number of titanium atoms with a valence of +3, and e is the number of oxygen atoms with a valence of +2, where 2a+3b+2c+3d=2e. As some more examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +3, d is the number of titanium atoms with a valence of +4, and e is the number of oxygen atoms with a valence of +2, where 2a+3b+3c+4d=2e.
[0039] According to the present application, the composite metal oxide is composed of FeTiO3, Fe2TiO5, Fe3Ti3O 10 , composite metal oxides formed by various different forms of oxides such as K2Ti3O7, Na2Ti3O7, CaTiO3 and MgTiO3.
[0040] In some embodiments, for the oxide containing iron, titanium and alkali metal elements, the general formula Fe (a+b) Ti (c+d) X f O e To illustrate, as some examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +2, d is the number of titanium atoms with a valence of +4, e is the number of oxygen atoms with a valence of +2, X is an alkali metal element, and f is the number of X atoms with a valence of +1, where 2a+3b+2c+4d+f=2e. As some other examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +2, d is the number of titanium atoms with a valence of +3, e is the number of oxygen atoms with a valence of +2, X is an alkali metal element, and f is the number of X atoms with a valence of +1, where 2a+3b+2c+3d+f=2e. As some further examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +4, d is the number of titanium atoms with a valence of +3, e is the number of oxygen atoms with a valence of +2, X is an alkali metal element, and f is the number of X atoms with a valence of +1, where 2a+3b+4c+3d+f=2e.
[0041] In other embodiments, for the oxide containing iron, titanium and alkaline earth metal elements, the general formula Fe (a+b) Ti (c+d) Y g O eTo illustrate, as some examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +2, d is the number of titanium atoms with a valence of +4, e is the number of oxygen atoms with a valence of +2, Y is an alkaline earth metal element, g is the number of Y atoms with a valence of +2, among which 2a+3b+2c+4d+2g=2e. As some other examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +3, d is the number of titanium atoms with a valence of +4, e is the number of oxygen atoms with a valence of +2, Y is an alkaline earth metal element, and g is the number of Y atoms with a valence of +2, wherein 2a+3b+3c+4d+2g=2e. As some more examples, a is the number of iron atoms with a valence of +2, b is the number of iron atoms with a valence of +3, c is the number of titanium atoms with a valence of +3, d is the number of titanium atoms with a valence of +2, e is the number of oxygen atoms with a valence of +2, Y is an alkaline earth metal element, and g is the number of Y atoms with a valence of +2, wherein 2a+3b+3c+2d+2g=2e.
[0042] In an embodiment of the present application, the metal elements in the composite metal oxide include iron elements of different valence states and titanium elements of different valence states. Here, the iron elements of different valence states and the titanium elements of different valence states are used as constituent elements in the composite metal oxide, and the two act synergistically. For example, the iron elements of different valence states and the titanium elements of different valence states interact and chemically combine (for example, oxidation-reduction reaction) at high temperature to form a composite metal oxide having an amorphous structure, which helps to improve the non-stick properties and other physical and chemical properties of the non-stick material.
[0043] In some embodiments, the metal elements in the composite metal oxide also include soluble metal elements and / or metal elements that can react with fatty acids in oils and fats. Specifically, the soluble metal elements are water-soluble metal elements, specifically including potassium elements and / or sodium elements. The metal elements that can react with fatty acids in oils and fats include calcium elements and / or magnesium elements. In the case where the composite metal oxide includes water-soluble metal elements (e.g., potassium elements, sodium elements), the composite metal oxide layer formed also includes water-soluble metal elements, which will dissolve and exchange during the use of the product, so that some nano-scale holes are generated on the surface of the composite metal oxide layer, thereby forming a micro-nano hydrophobic structure, so that better non-stickiness can be produced under the infiltration of oil molecules. In addition, in the case where the composite metal oxide includes metal elements that can react with fatty acids in oils and fats (e.g., calcium elements, magnesium elements), the composite metal oxide layer formed also naturally includes metal elements that can react with fatty acids in oils and fats, so that the composite metal oxide layer is easy to react with fatty acids in oils and fats, and the formed fatty acid salts are deposited on the surface of the composite metal oxide layer, which can further assist in providing non-stickiness. It should be noted that only some specific examples of water-soluble metal elements and metal elements that can react with fatty acids in oils and fats are shown here. However, those skilled in the art will understand that other water-soluble metal elements and metal elements that can react with fatty acids in oils and fats can achieve technical effects equivalent to those of the present application.
[0044] In some embodiments, the non-stick material further comprises a carbonized product of a binder, and the carbonized product of the binder is dispersed in the composite metal oxide, specifically, the carbonized product of the binder is dispersed between adjacent particles of the composite metal oxide.
[0045] In these embodiments, carbonized products of the binder are dispersed in the particles of the composite metal oxide. On the one hand, the presence of the carbonized products of the binder can facilitate the connection of the various particles of the matrix and ensure the internal bonding strength of the various particles of the non-stick material. On the other hand, using the carbonized products of the binder as a connecting bridge between the various particles of the matrix can make the non-stick material as a whole present higher hardness and stability.
[0046] Specifically, the carbonization product of the binder is a lipophilic carbonization product, so that the lipophilicity of the composite metal oxide layer formed by the non-stick material can be ensured during subsequent use, which is beneficial to the locking of oil molecules, thereby further improving the non-stick performance of the composite metal oxide layer due to the non-stick principle of the oil film.
[0047] In some embodiments, in the non-stick material, the weight ratio of the carbonized product of the binder to the composite metal oxide is (0.4-3.5):(96.5-99.6). The carbonized product of the binder and the composite metal oxide have a suitable weight ratio, so that excessive carbonized product of the binder can be prevented from affecting the overall strength of the non-stick material.
[0048] In some embodiments, the non-stick material is in a granular form and has a three-dimensional macroporous structure. The porosity of a single particle of the non-stick material is 25%-55%, and the pore size is 500 nanometers-4 micrometers. The pores are interconnected and naturally stacked in an irregular arrangement to form a three-dimensional macroporous structure, so as to facilitate the formation of a composite metal oxide layer with three-dimensional pores.
[0049] In these embodiments, a composite metal oxide having a three-dimensional macroporous structure is used as a non-stick material, which can be formed into a composite metal oxide layer having a three-dimensional pore structure through melt stacking. In this way, edible oil can be well adsorbed and stored, thereby further enhancing the non-stick properties of the product having the composite metal oxide layer.
[0050] In some embodiments, the non-stick material obtained by spray drying and sintering is a material in which the volume percentage of the amorphous phase is in the range of 30%-65%. Such a non-stick material in which the volume percentage of the amorphous phase is high has low surface energy and higher wear resistance and stability.
[0051] In other embodiments, the non-stick material after high-temperature sintering can also be subjected to rapid cooling treatment, so that the atoms or molecules inside it do not have time to arrange into an ordered crystal structure, and the degree of amorphization of the non-stick material is further improved, so as to better achieve the purpose of improving non-stickiness. Specifically, the specific method of rapid cooling treatment includes heating the composite metal oxide layer and quickly exposing it to a low-temperature environment to achieve rapid cooling, so that the material in the composite metal oxide layer does not have time to crystallize, and thus tends to amorphous transformation. Specifically, the composite metal oxide layer is sintered (sintering temperature is 1200℃-1400℃, sintering time is 4h), and then cooled at a cooling rate of 80℃ / s-100℃ / s. As an example, the volume proportion of the amorphous phase of the non-stick material is 35%-70%.
[0052] In summary, the volume proportion of the amorphous phase of the non-stick material according to the present application is 30%-70%. In a preferred embodiment, the volume proportion of the amorphous phase of the non-stick material is 50%-70%.
[0053] In some embodiments, the non-stick material is a granulated powder particle with an average particle size of 10 microns to 70 microns. In a preferred embodiment, the particles of the non-stick material are normally distributed, and D50 is 25 microns to 35 microns. In this way, on the one hand, a composite metal oxide layer with a suitable pore structure can be formed by the non-stick material of this particle size, thereby facilitating oil storage and improving non-stickiness; on the other hand, the granulated powder particles themselves have a large specific surface area, which can ensure the bonding force between the composite metal oxide layer and the substrate.
[0054] According to a second aspect of the present application, a non-stick cooker is provided. Figure 4 and Figure 5 As shown, the non-stick cookware includes a substrate 110 and a composite metal oxide layer 120 formed on the inner surface of the substrate 110, wherein the composite metal oxide layer 120 is formed by spraying according to the non-stick material described above. Specifically, the composite metal oxide layer has an amorphous structure, the metal elements in the composite metal oxide layer include iron elements of different valence states and titanium elements of different valence states, the surface of the composite metal oxide layer has a concave-convex structure, and the concave parts of the concave-convex structure are filled with low surface energy materials. Here, the composite metal oxide layer itself has a low surface energy and has a certain initial non-stick performance. In addition, the composite metal oxide layer will not age with the extension of the use time, and has good physical and chemical stability. Therefore, it can have a more durable and long-lasting non-stick performance. In addition, the composite metal oxide layer has a concave-convex structure, which can protect low surface energy materials with lower surface energy than its surface energy, and further improve the non-stick performance of the non-stick cookware.
[0055] In some embodiments, carbonization products of a binder are also dispersed in the composite metal oxide layer.
[0056] In these embodiments, carbonized products of the binder are dispersed in the composite metal oxide layer. On the one hand, the presence of the carbonized products of the binder can facilitate the connection of the various particles of the composite metal oxide and ensure the internal bonding force of the various particles of the composite metal oxide. On the other hand, using the carbonized products of the binder as a connecting bridge between the various particles of the matrix can make the composite metal oxide layer as a whole present higher hardness and stability.
[0057] In some embodiments, in the composite metal oxide layer, a weight ratio of the carbonization product of the binder to the composite metal oxide is (0.4-3.5):(96.5-99.6).
[0058] According to the present application, the composite metal oxide layer can be formed by thermal spraying the composite metal oxide, wherein the composite metal oxide is a microsphere having a three-dimensional macroporous structure. During the thermal spraying process, the surface of the microsphere of the composite metal oxide is heated and further densely stacked on the substrate as a whole to form a composite metal oxide layer, so that the formed composite metal oxide layer can have a more delicate pore structure than the three-dimensional macroporous structure of the composite metal oxide, and itself presents a three-dimensional pore structure. It can be understood that the three-dimensional pore structure in the composite metal oxide layer is largely determined by the three-dimensional macroporous structure of the microsphere.
[0059] As an example, in the formed composite metal oxide layer, there is a three-dimensional pore structure, the porosity of the composite metal oxide layer is 5%-30%, and the pore size is 500 nanometers-4 micrometers, preferably, the pore size is 500 nanometers-1 micrometer. More specifically, the three-dimensional pore structure includes a plurality of macropores located between the microspheres and a plurality of small pores located inside the microspheres, the size of the macropores is 900 nanometers-4 micrometers, and the size of the small pores is 500 nanometers-900 nanometers. The macropores can make it easy for oil molecules or oils to enter the composite metal oxide layer, and the small pores can make it easy for oil molecules or oils to remain, so that the non-stick performance of the cookware with the composite metal oxide layer can be guaranteed due to the stable release of the oil film.
[0060] In some embodiments, the composite metal oxide layer is formed by thermal spraying of the composite metal oxide. Thermal spraying includes flame spraying, arc spraying and plasma spraying. Taking plasma spraying as an example, the specific parameters are: powder feeding speed 10g / min-25g / min, spraying distance 150mm-200mm, arc current 350A-500A, voltage 50V-70V, hydrogen pressure 0.6MPa-0.8MPa, hydrogen flow rate 200L / h-300L / h, argon pressure 1.0MPa-1.5MPa, argon flow rate 1000L / h-2000L / h, workpiece linear speed 25m / min-35m / min.
[0061] In some embodiments, the thickness of the composite metal oxide layer is in the range of 10 micrometers to 150 micrometers, which can ensure the long-lasting non-stick performance of the cookware having the composite metal oxide layer.
[0062] According to the present application, after the composite metal oxide layer is obtained by spraying, the composite metal oxide layer can be polished and ground to make the surface bright and smooth for easy stir-frying. If necessary, edible oil can be used to coat the surface of the composite metal oxide layer, and then baked at 250°C-350°C to maintain the pot and improve the non-stick and rust-proof effects.
[0063] According to the present application, when the composite metal oxide includes water-soluble metal elements (e.g., potassium elements, sodium elements), the composite metal oxide layer formed also includes water-soluble metal elements, which will dissolve and exchange during the use of the product, so that some nanometer-scale holes are generated on the surface of the composite metal oxide layer, thereby forming a micro-nano hydrophobic structure, so that better non-stickiness can be produced under the infiltration of oil molecules. In addition, when the composite metal oxide includes metal elements that can react with fatty acids in oils and fats (e.g., calcium elements, magnesium elements), the composite metal oxide layer formed also naturally includes metal elements that can react with fatty acids in oils and fats, so that the composite metal oxide layer is easy to react with fatty acids in subsequent oils and fats as oil molecules, so as to form a fatty acid salt modified layer on the surface of the composite metal oxide layer, thereby further improving non-stickiness. Therefore, the surface of the composite metal oxide layer includes a fatty acid salt modified layer formed by reacting with the metal elements in the composite metal oxide layer.
[0064] According to the present application, the concave-convex structure of the composite metal oxide layer is at the micron level and is composed of a plurality of convex hulls. The height of the convex hulls is 100μm-500μm, the width is 200μm-400μm, and the spacing between adjacent convex hulls is 200μm-400μm. The low surface energy material is formed at least in the depressions of the concave-convex structure. As an example, a low surface energy material is arranged in the depressions between adjacent convex hulls. The low surface energy material here is protected by the composite metal oxide layer and is not easily damaged by a spatula, so as to improve the non-stick life of the product. As another example, the low surface energy material fills the depressions of the concave-convex structure and covers the surface of the concave-convex structure, so that a more lasting non-stick performance can be achieved.
[0065] According to the present application, the substrate has a concavo-convex surface, and the composite metal oxide layer formed thereon is also stacked on the substrate in a concavo-convex form, that is, when the substrate is concavo-convex, the composite metal oxide layer also presents a corresponding concavo-convex shape. Of course, the present application is not limited to this, and a concavo-convex structure can also be re-formed on the formed flat composite metal oxide layer.
[0066] like Figure 5 As shown, the non-stick cookware includes a substrate 110 and a composite metal oxide layer 120 stacked on the substrate 110. The surface of the composite metal oxide layer 120 has a concave-convex structure, and a low surface energy material 150 is formed at the concave parts of the concave-convex structure.
[0067] In these embodiments, by forming a composite metal oxide layer having a concave-convex structure on the surface with a composite metal oxide including a composite metal oxide, on the one hand, the demand for manufacturing patterned metal cookware can be met, and on the other hand, non-stick cookware with better non-stick performance can be obtained by cooperating with low surface energy materials.
[0068] According to the present application, the vertical distance h from the highest point of the protrusion of the concave-convex structure to the lowest point of the depression of the concave-convex structure is 0.05mm-0.3mm, the top width w1 of the protrusion is 1mm-3mm, and the bottom width w2 of the protrusion is 3mm-4mm.
[0069] Here, the low surface energy material can be a silane material, an oil molecule, a fluorine coating or a ceramic coating, as long as the surface energy of the material is lower than the surface energy of the composite metal oxide layer, and this application does not make too many restrictions on this. The low surface energy material can fill the entire depression, or it can have a preset distance from the mouth of the depression. Here, the preset distance is not greater than the vertical distance h, and can be 0.03mm-0.25mm.
[0070] According to the present application, the substrate can be made of conventional metal materials. The composite metal oxide belongs to a type of ceramic material and has relatively poor bonding strength with the metal substrate. In order to increase the bonding strength between the composite metal oxide layer and the substrate. In some embodiments, the non-stick cookware also includes a transition layer 130, which is arranged between the substrate 110 and the composite metal oxide layer 120, and the transition layer 130 is made of a metal material. Specifically, the transition layer can be prepared by a metal material through a thermal spraying or cold spraying method. The transition layer material selects a conventional metal material, for example, at least one of titanium, titanium alloy, iron, iron alloy, aluminum, aluminum alloy, zinc, zinc alloy, copper, copper alloy, zirconium and zirconium alloy. It is preferably titanium or titanium alloy, which can ensure bonding strength on the one hand and have higher strength on the other hand.
[0071] In an exemplary embodiment, the thickness of the transition layer is in the range of 10 microns to 80 microns.
[0072] According to a third aspect of the present application, a method for manufacturing non-stick cookware is provided, wherein the method for manufacturing non-stick cookware comprises: forming a mixed slurry including a binder and a base material, wherein the base material includes titanium oxide and ferrosoferric oxide; spray-drying the mixed slurry to obtain non-stick particles; sintering the non-stick particles to slightly melt the base material in the non-stick particles, thereby obtaining a composite metal oxide including iron elements of different valence states and titanium elements of different valence states and having an amorphous structure; and spraying the composite metal oxide on a substrate to form a composite metal oxide layer on the substrate, thereby manufacturing non-stick cookware having a composite metal oxide layer.
[0073] According to the manufacturing method of non-stick cookware provided by the embodiment of the present application, by spray drying the mixed slurry including the binder and the base material, and then sintering, a composite metal oxide having an amorphous structure and containing iron elements of different valence states and titanium elements of different valence states can be formed, the composite metal oxide has a low surface energy, and the composite metal oxide layer formed by it can have good initial non-stick properties. In addition, the composite metal oxide layer formed by the composite metal oxide does not age with the extension of the use time, has good physical and chemical stability, and therefore has more durable and long-lasting non-stick properties. In addition, the composite metal oxide has a three-dimensional macroporous structure and is in the shape of a microsphere. The composite metal oxide layer formed by this composite metal oxide can retain the three-dimensional macroporous structure of the microsphere as much as possible, thereby forming a composite metal oxide layer with a corresponding three-dimensional pore structure. The composite metal oxide layer with a corresponding three-dimensional pore structure is easy to adsorb oil molecules, so that it can exert a more excellent non-stick performance due to the oil film non-stick principle.
[0074] Hereinafter, a method for manufacturing non-stick cookware according to the present application will be described with specific embodiments.
[0075] Formation of composite metal oxides
[0076] According to the present application, the manufacturing method of non-stick cookware includes the step of preparing a composite metal oxide. The step of preparing the composite metal oxide includes forming a mixed slurry including a binder and a base material, wherein the base material includes titanium oxide and ferrosoferric oxide; spray drying the mixed slurry to obtain non-stick particles; sintering the non-stick particles to slightly melt the base material in the non-stick particles, thereby obtaining a composite metal oxide including iron elements of different valence states and titanium elements of different valence states and having an amorphous structure.
[0077] As some embodiments, the binder includes an alcohol binder and / or a cellulose binder. As some other examples, the binder includes an oleophilic binder.
[0078] Specifically, the cellulose binder includes at least one of hydroxymethyl cellulose binder, hydroxyethyl cellulose binder and hydroxypropyl cellulose binder, and the alcohol binder may include at least one of polyvinyl alcohol binder, polypropylene alcohol binder and other higher alcohol binders containing more than six carbon atoms. However, the present application is not limited thereto, but a suitable binder can be selected according to actual needs.
[0079] It should be noted that the binder according to the present application will volatilize or carbonize during the subsequent sintering process. Whether it is volatilization or carbonization depends largely on the heating rate, sintering temperature and time of the subsequent sintering stage. Here, carbonization is the process in which organic matter is thermally decomposed at high temperature to remove hydrogen, oxygen, etc. other than carbon as low molecular compounds, leaving only residual carbon. Volatilization is the process in which organic matter changes from liquid to gas after reaching the boiling point, that is, in this process, the binder in the non-stick particles will change to gas and leave pores on the non-stick particles.
[0080] Provide base material
[0081] According to the present application, the base material includes titanium oxide and ferroferric oxide, which at least form a mixed slurry with a binder and can be spray-dried (powder granulated) to form a composite metal oxide with an amorphous structure. Here, titanium oxide and ferroferric oxide refer to substances, not components. In these embodiments, titanium and iron are non-toxic and harmless metals and can form stable insoluble oxides. The electronic configuration of titanium is 1s22s2 2p 6 3s2 3p 6 3d2 4s2 (2 / 8 / 10 / 2), the iron electron configuration is 1s 2 2s 2 2p 6 3s 2 3p 6 3d 6 4s 2 (2 / 8 / 14 / 2), titanium and iron are both transition metal elements, and their electron layer arrangements are similar in the periodic table, so these two elements are very easy to form composite metal oxides (multinary oxides) in oxides. Secondly, the atomic radius of titanium is 0.145 nanometers, and the atomic radius of iron is about 0.124 nanometers. Due to the obvious difference in the atomic radius of the two elements, the two atoms occupy different volumes in the lattice arrangement, which causes the lattice to be distorted instead of forming a complete and standard lattice arrangement, so that the formed composite oxide has certain amorphous properties, thereby further improving the non-stick performance.
[0082] In some embodiments, the base material is titanium oxide and ferroferric oxide. In other embodiments, the base material may include water-soluble metal oxides and / or metal oxides that can react with fatty acids in oils and fats in addition to titanium oxide and ferroferric oxide. The water-soluble metal oxides are alkali metal oxides, and the metal oxides that can react with fatty acids in oils and fats are alkaline earth metal oxides. Specifically, the alkali metal oxides include potassium oxide and / or sodium oxide, and the alkaline earth metal oxides include calcium oxide and / or magnesium oxide.
[0083] In these embodiments, titanium oxide and ferrosoferric oxide are used as main materials, and water-soluble metal oxides and / or metal oxides capable of reacting with fatty acids in oils and fats are used as auxiliary materials. By introducing auxiliary materials larger than titanium and iron as part of the base material, the lattice distortion can be further aggravated, thereby facilitating the formation of a composite metal oxide with obvious amorphous characteristics.
[0084] In a preferred embodiment, the base material is titanium oxide, ferroferric oxide, potassium oxide, sodium oxide, calcium oxide and magnesium oxide. Among them, the atomic radius of titanium is 0.145 nanometers, the atomic radius of iron is about 0.124 nanometers, the atomic radius of calcium is 0.223 nanometers, the atomic radius of magnesium is 0.160 nanometers, the atomic radius of sodium is 0.186 nanometers, and the atomic radius of potassium is 0.236 nanometers. There is a significant difference in the atomic radius of the two elements of titanium and iron. The two atoms occupy different volumes in the lattice arrangement, which leads to the distortion of the lattice instead of forming a complete and standard lattice arrangement. Therefore, the composite oxide has certain amorphous properties, and the introduction of alkali metals and alkaline earth metals with larger atomic radii further aggravates the lattice distortion, which is more conducive to the formation of composite oxides with outstanding amorphous properties (larger amorphous volume proportion or amorphous degree). During the sintering process, titanium oxide, ferroferric oxide, potassium sodium oxide and calcium magnesium oxide are semi-melted, so that the atoms of titanium, iron, potassium, sodium, calcium and magnesium are reorganized to form a new composite oxide, that is, a composite metal oxide including titanium iron oxide, titanium potassium oxide, titanium sodium oxide, titanium calcium oxide or titanium magnesium oxide.
[0085] In these embodiments, the oxides in the base material, such as titanium oxide and ferrosoferric oxide, can react chemically under the influence of the high temperature of subsequent sintering to form a composite metal oxide having an amorphous structure. Furthermore, under the influence of the content of the base material and the binder, a composite metal oxide having a desired three-dimensional macroporous structure is formed.
[0086] In some embodiments, the base material is spherical or quasi-spherical, and the composite metal oxide with a three-dimensional macroporous structure formed therefrom is also spherical. Specifically, it is a micron-level sphere (microsphere), and the microsphere has a relatively uniform pore distribution and a high through-pore porosity, which is not only conducive to the adsorption and storage of oils, but also ensures the mechanical strength and wear resistance of the formed microspheres. The coating formed by the microspherical composite metal oxide can ensure that oil molecules can easily enter, and the composite metal oxide can effectively protect the oil molecules relatively located inside, avoiding direct contact with the heat source and volatilization. In addition, the composite metal oxide can effectively reduce the conduction and diffusion of heat, reduce the possibility of direct contact of oil molecules with high temperatures, thereby improving the stability and safety of the composite metal oxide.
[0087] In some embodiments, the base material is of micron level, specifically, the particle size of the base material is 0.05 micron-5 micron. When the base material is in the range of 0.05 micron-5 micron, it is easier to form the above-mentioned composite metal oxide with an amorphous structure and a three-dimensional macroporous structure, and the porosity of the composite metal oxide layer formed can be controlled to easily meet the needs of locking oils. It should be noted that the particle size of the above-mentioned material can be the maximum length of each particle, rather than specifically limiting the material to have a spherical or spherical shape. For example, but not limited to, when the material has an elliptical shape, the particle size of the material can refer to the length of its major axis. It should be noted that the micron-level base material can be obtained by crushing and grinding, or by commercially available methods, and the present application does not make too many restrictions on this.
[0088] In a preferred embodiment, the particle size of the base material forming the mixed slurry is normally distributed, the base material is a mixture of multiple particles, and the particle size R of the mixture has multiple distribution intervals. Among them, the multiple distribution intervals include a first distribution interval R1, a second distribution interval R2, and a third distribution interval R3, wherein 0.05 microns ≤ R1 ≤ 0.1 microns, the second distribution interval is 0.1 microns < R2 ≤ 1 micron, and the third distribution interval is 1 micron < R3 ≤ 5 microns. Among them, based on the total volume of the base material in the mixture as 100%, the volume of the base material with a particle size in the first distribution interval accounts for 20%-40%, the volume of the base material with a particle size in the second distribution interval accounts for 35%-65%, and the volume of the base material with a particle size in the third distribution interval accounts for 10%-25%.
[0089] Forming mixed slurry
[0090] According to the present application, the method for preparing the composite metal oxide further comprises the step of forming a mixed slurry. Specifically, the step of forming the mixed slurry comprises providing a base material and a binder, and then ball-milling the base material and the binder to form a mixed slurry.
[0091] Specifically, the base material and the binder are added to a ball mill, and deionized water is added as a grinding medium, and the grinding is performed for 4h-8h to obtain a uniformly dispersed mixed slurry including the base material and the binder. The binder in the mixed slurry can enhance the bonding force between the particles forming the composite metal oxide to form a stable particle stack, so that the composite metal oxide has a certain mechanical strength to ensure the stability of the composite metal oxide layer formed later, and avoid crushing and affecting the formation of the three-dimensional pore structure of the composite metal oxide layer. It should be noted that in the step of forming the mixed slurry, a certain amount of dispersant can also be included so that each particle of the base material is easy to be more evenly dispersed in the mixed slurry.
[0092] In some embodiments, the mixed slurry includes a base material and a binder, and the weight ratio of the base material to the binder is (52-70): (30-48). In the mixed slurry, the weight proportion of the binder is equivalent to that of the base material, so much binder will volatilize in the subsequent steps, so that it is easy to form a composite metal oxide with a three-dimensional macroporous structure while ensuring the overall strength, so that the composite metal oxide layer formed by the composite metal oxide can retain the three-dimensional macroporous structure of the composite metal oxide, thereby ensuring the formation of a three-dimensional pore structure of the composite metal oxide layer.
[0093] According to the present application, the weight proportion of each oxide in the base material can enable each oxide in the base material to react as fully as possible under the influence of high temperature to form a composite metal oxide.
[0094] In other embodiments, the base material is titanium oxide and ferroferric oxide. As an example, the weight ratio of titanium oxide and ferroferric oxide is (13-39): (13-39). Within this ratio range, titanium oxide and ferroferric oxide can easily form a composite metal oxide through chemical reaction at a high temperature of subsequent sintering, and can minimize the impact of the unreacted part on the overall composite metal oxide. In addition, within this ratio range, the synergistic effect of titanium oxide and ferroferric oxide can help increase the degree of amorphization of the composite metal oxide.
[0095] In some embodiments, the base material includes titanium oxide and ferroferric oxide, and may also include water-soluble metal oxides and / or metal oxides that can react with fatty acids in oils and fats. As an example, the water-soluble metal oxide may be an alkali metal oxide, and the metal oxide that can react with fatty acids in oils and fats may be an alkaline earth metal oxide. Wherein, considering the safety of the reaction and the subsequent effect product of the composite metal oxide, the water-soluble metal oxide may include potassium oxide and / or sodium oxide, which may also be referred to as potassium sodium oxide; the metal oxide that can react with fatty acids in oils and fats includes calcium oxide and / or magnesium oxide, which may also be referred to as alkaline earth metal oxide. In a preferred embodiment, the base material includes titanium oxide, ferroferric oxide, water-soluble metal oxides and metal oxides that can react with fatty acids in oils and fats. As an example, the ratio of titanium oxide, ferroferric oxide, water-soluble metal oxides and metal oxides that can react with fatty acids in oils and fats is (13-39): (13-39): (1-2): (1-2), and the proportion of each substance is such that a composite metal oxide with a higher volume proportion of amorphous phase of an amorphous structure can be formed to facilitate the improvement of non-stickiness. As a specific example, the ratio of titanium oxide, ferrosoferric oxide, alkali metal oxide and alkaline earth metal oxide is (13-39):(13-39):(1-2):(1-2).
[0096] It should be noted that in the above embodiments, the melting point of alkali metal oxides is relatively low. When the base material includes sodium oxide and potassium oxide, the melting point of the entire base material can be lowered, which can facilitate the base material to be in a slightly molten state during the sintering process.
[0097] Spray drying to form non-stick granules
[0098] After the pulping is completed, the mixed slurry is spray dried. According to some embodiments of the present application, a spray drying device (such as a pressure spray dryer, a centrifugal spray dryer, etc.) is used to atomize the mixed slurry into fine droplets. The atomized droplets come into contact with hot air, the solvent (water) evaporates rapidly, and the particles of the base material form a basic structure of microspheres with the binder. As an example, the mixed slurry can be conveyed to a high-speed atomization disk to form droplets, and then the droplets are blown into a drying tower using hot air. The droplets stay for a short time during the descent process and eventually form wet microspheres (non-stick particles).
[0099] According to the present application, by adjusting the process parameters of spray drying (e.g., atomizing disk rotation speed and hot air temperature), the particle size, pore size and distribution characteristics of the microspheres can be controlled. As an example, during the high-speed movement of the atomizing disk, by controlling the rotation speed of the atomizing disk, the mixed slurry can be dispersed into fine and uniform droplets, thereby improving the molding quality and consistency of the microspheres. In some embodiments, the rotation speed of the atomizing disk can be controlled within the range of 4000 rpm-15000 rpm, preferably, it can be controlled within the range of 6000 rpm-12000 rpm. According to some embodiments of the present application, the temperature of the hot air can be controlled within the range of 60°C-100°C, the temperature of the drying tower can be controlled within the range of 100°C-400°C, and the short residence time of the droplets in the drying tower can be controlled to be 5 seconds-15 seconds. The relatively low temperature hot air can reduce the loss of binder, so that the water in the obtained preformed wet microspheres can be volatilized and sufficient binder can be retained, thereby ensuring that microspheres with a porous structure can be formed by volatilization or carbonization of the binder during the subsequent sintering process.
[0100] Sintering of spray-dried non-stick particles
[0101] According to the present application, the base material itself does not have pores, and the mixed slurry including the base material and the binder is spray-dried and sintered at high temperature to lay the foundation for the subsequent formation of a three-dimensional macroporous structure, thereby forming microspheres with a three-dimensional macroporous structure and an amorphous structure. Here, the base material is slightly melted during the high-temperature sintering process, and its physical state gradually changes from a solid state to a semi-solid state or a viscous state, so that each base material diffuses with each other and chemically combines to form a composite metal oxide according to the present application.
[0102] According to the preparation method of the composite metal oxide of the present application, the non-stick particles obtained after spray drying are sintered. According to some embodiments of the present application, the spray-dried microspheres can be heated to a temperature above the carbonization temperature at a high heating rate under an inert atmosphere such as nitrogen and argon, and maintained for a long time, so that as much binder as possible is carbonized in this process. As an example, the non-stick particles are placed in a sintering furnace under an inert atmosphere such as nitrogen and argon. The initial sintering temperature is 20°C-30°C, and the heating rate is 15°C / minute-20°C / minute. The larger heating rate can volatilize the binder at this stage, and the temperature is increased to 500°C-650°C at a heating rate of 15°C / minute-20°C / minute, and the temperature is kept for 6h-8h, so that the binder in the spray-dried microspheres is carbonized as much as possible. Then, the temperature is raised to 1200°C-1250°C at a heating rate of 55°C / min-100°C / min, and then kept warm for 12h-24h. During this process, titanium oxide and ferrosoferric oxide interact with each other, such as diffusion and reaction, thereby changing the original crystal structure to form a composite metal oxide with an amorphous structure. In addition, the particles of adjacent base materials interact with each other to fit together in the contact part, shrink in volume, and leave pores between the particles, and finally form a composite metal oxide with a certain three-dimensional macroporous structure and a carbonized product of a binder. In addition, during the sintering process, the contacting base materials fit together in the contact part after sintering to form microspheres, so that the particles of the microspheres have a sufficiently strong binding force to ensure the stability of the microspheres in subsequent processes.
[0103] In these embodiments, under an inert atmosphere such as nitrogen and argon, at a faster heating rate, a higher sintering temperature and a longer sintering time, a small portion of the binder will volatilize, leaving pores, and most of the binder will be carbonized to form a material with a high carbon content (the carbonization product of the binder), and adjacent particles will interact to form a material having a stack of composite metal oxide particles and carbonization products dispersed in the composite metal oxide.
[0104] As an example, the carbonization temperature of the binder of the present application is roughly between 350°C and 600°C. Under the influence of the subsequent sintering temperature and time, most of the binder will volatilize and reserve pores in the composite metal oxide, and a small part of the binder will form a carbonized product. Since the carbonized product of the binder is mainly composed of non-polar carbon elements and has a certain lipophilicity, the composite metal oxide layer of the cookware formed by this composite metal oxide is easier to be filled with oil molecules.
[0105] In some embodiments, 90% of the binder volatilizes, while 10% of the binder carbonizes, and the carbonized product of the binder adheres to a portion of the surface of the composite metal oxide particles. Specifically, the weight ratio of the carbonized product of the binder to the composite metal oxide is defined as (0.4-3.5):(96.5-99.6).
[0106] In these embodiments, the composite metal oxide also contains a small amount of carbonized product of the binder. Since the carbonized product of the binder is mainly composed of non-polar carbon elements and has a certain lipophilicity, it can further enhance the overall lipophilicity of the composite metal oxide, making the composite metal oxide layer formed thereby easier to fill with oil molecules.
[0107] According to the present application, a composite metal oxide (for example, a composite of titanium iron oxide, titanium potassium oxide, titanium sodium oxide, titanium calcium oxide and titanium magnesium oxide) can be formed as a non-stick material by spray drying and high-temperature sintering. Since iron has divalent and trivalent valences, titanium has divalent and tetravalent valences, and there are univalent alkali metals and divalent alkaline earth metal elements, various oxide forms may be obtained in the process of forming the composite oxide, and its main forms include FeTiO3, Fe2TiO5, Fe3Ti3O 10 , K2Ti3O7, Na2Ti3O7, CaTiO3, MgTiO3, the composite oxides formed by various oxides in different forms have irregular and disordered states in the microscopic lattice arrangement and present amorphous characteristics as a whole.
[0108] Figure 1 This is a scanning electron microscope image of a non-stick particle provided according to an embodiment of the present application. Figure 2 is a scanning electron microscope image of a composite metal oxide provided in an embodiment of the present application. Figure 1 It can be seen that before sintering, the non-stick particles do not have obvious pores. Figure 2 It can be seen that in the composite metal oxide obtained by sintering the non-stick particles, the composite metal oxide has an obvious three-dimensional macroporous structure, and the pores of the three-dimensional macroporous structure are generally evenly distributed.
[0109] Figure 3 is an XRD spectrum of a composite metal oxide provided in an embodiment of the present application. Figure 3 As shown, the characteristic peaks are not particularly obvious, the miscellaneous peaks are numerous and disordered, and the crystallinity is poor. It can be seen that the crystallinity of the composite metal oxide is general and has amorphous characteristics. According to the conventional full spectrum fitting method, the amorphous phase volume proportion of the composite metal oxide is 60%.
[0110] According to the method for manufacturing a composite metal oxide of the present application, the microsphere particles obtained by sintering can also be sieved after the sintering step to obtain microspheres of different particle size ranges. Microsphere powders of different particle size ranges can be sieved as needed to be applied to different products. For example, the sintered powder is vibrated and sieved to obtain spherical or quasi-spherical microspheres with a particle size of 10 μm-45 μm.
[0111] According to the present application, the microsphere particles finally formed do not refer to only one particle in terms of quantity, but may be a plurality of particles gathered together. The particle size of the microsphere particles finally formed is not less than the particle size of the original various powders.
[0112] In some embodiments, the composite metal oxide is in the form of micron-scale particles. As an example, the average particle size of the composite metal oxide is 10 microns to 70 microns, and D50 (median particle size) is 25 microns to 35 microns. If the average particle size of the non-stick powder is greater than 10 microns, it is easy to clog the powder feeding pipe, and the powder melting degree is not enough, the bonding force of the composite metal oxide layer is reduced, and the coating quality is reduced; if the average particle size of the non-stick powder is less than 70 microns, the powder fluidity is poor, and the flight speed during the spraying process is not enough, it is easy to over-melt, and the deposition efficiency and coating quality are reduced.
[0113] According to the present application, there are pores inside or between the microsphere particles after spray drying, which can allow gas or liquid to pass through, and the pores of the three-dimensional macroporous structure in the microspheres formed by spray drying in the present application are mostly open pores or connected pores, that is, through pores, and a few are closed pores, so that the oil storage capacity of the formed composite metal oxide layer can be guaranteed. As an example, the volume of the through pores accounts for about 80%-90%, and the rest is closed pores.
[0114] Provide substrate
[0115] According to the present application, the substrate 110 can be made of commonly used materials. For example, the material can be stainless steel, titanium, aluminum, their corresponding alloys and composite materials. The substrate 110 can have a shape corresponding to the function, for example, Figure 4 As shown in FIG. 1 , when the non-stick cookware 100 is a non-stick pan, the base 110 may have a conventional pan shape. It should be understood that Figure 4 Only the main body of the non-stick pan is exemplarily shown without showing other parts, and the non-stick pan according to the present invention may also include common cookware structures / components such as a handle (eg, a pot handle).
[0116] In some embodiments, the inner surface of the substrate is a concave-convex surface, that is, the inner surface of the substrate is uneven. Here, the concave-convex surface can also be prepared by etching, laser engraving, stamping, etc., and the present application does not impose too many restrictions on this.
[0117] Forming a transition layer (optional)
[0118] In some embodiments, a rough transition layer is provided between the substrate and the composite metal oxide layer, and the rough transition layer can further enhance the bonding force between the coating and the substrate. As an example, the rough transition layer can be formed by thermally spraying a metal material on the surface of the substrate. Specifically, the metal material can include at least one of titanium, titanium alloy, iron, iron alloy, aluminum, aluminum alloy, zinc, zinc alloy, copper, copper alloy, zirconium and zirconium alloy.
[0119] Formation of a composite metal oxide layer from a composite metal oxide
[0120] According to the present application, the composite metal oxide layer can be obtained by thermal spraying the composite metal oxide as described above. The composite metal oxide layer can also be modified by rapid cooling.
[0121] According to the present application, before the quenching treatment, the volume proportion of the amorphous phase of the composite metal oxide layer is 30%-50%. After the quenching treatment, the volume proportion of the amorphous phase of the composite metal oxide layer increases, specifically 50%-70%. Here, by increasing the volume proportion of the amorphous phase of the composite metal oxide layer (the degree of amorphization), the non-stick performance of the composite metal oxide layer as a whole is further improved.
[0122] In some embodiments, for the specific method of rapid cooling treatment, the composite metal oxide layer can be heated and quickly exposed to a low temperature environment to achieve rapid cooling, so that the material in the composite metal oxide layer does not have time to crystallize, and thus tends to amorphous transformation. Specifically, the composite metal oxide layer is sintered (sintering temperature is 1200°C-1400°C, sintering time is 4h), and then cooled at a cooling rate of 80°C / s-100°C / s.
[0123] According to the present application, when the composite metal oxide in the form of microspheres is sprayed to form a composite metal oxide layer, only the surface thereof is slightly melted so as to be stacked on the substrate to form a composite metal oxide layer. The three-dimensional macroporous structure of the microspheres can be retained as much as possible in the composite metal oxide layer, thereby forming a composite metal oxide layer with a three-dimensional pore structure. The pores of the composite metal oxide layer with a three-dimensional pore structure match the oil molecules, and are easy to adsorb the oil molecules, and can lock the oil molecules with a certain adhesion force, so that the oil molecules can be slowly released, thereby being able to exert excellent non-stick properties due to the oil film non-stick principle. In addition, the base material forming the composite metal oxide is relatively small, at the micron level, and has a large specific surface area when combined with the substrate, thereby being able to ensure the bonding force with the substrate. The base material has good wear resistance and can serve as a protector for oil molecules, thereby being able to ensure that the cookware having the composite metal oxide layer has a continuous and stable oil film and ensures a long-lasting non-stick performance.
[0124] According to an embodiment of the present application, the low surface energy material includes at least one of silane materials, oil molecules, fluorine coatings and ceramic coatings. The formation of the low surface energy material on the composite metal oxide layer will be specifically described in the following two embodiments.
[0125] (1) Modification of composite metal oxide layer with silane materials
[0126] In the embodiments of the present application, before modification, the composite metal oxide layer may be treated with an acid or alkali solution to increase the surface roughness of the composite metal oxide layer, thereby providing more binding sites for the modified material.
[0127] According to the present application, the method for manufacturing non-stick cookware further includes the step of modifying the composite metal oxide layer with a silane material. Specifically, the step of modifying the composite metal oxide layer with a silane material includes the step of providing a modified solution including a silane material and water. The step of providing a modified solution including a silane material includes the step of preparing a modified solution including a silane material and water. Here, by grafting a low surface energy material onto the composite metal oxide layer, the overall non-stick performance of the composite metal oxide layer is further improved.
[0128] In an exemplary embodiment, the step of preparing a modified solution including a silane material and water includes providing a silane material, providing an aqueous solvent, and mixing the silane material with the aqueous solvent to prepare a modified solution including the silane material and water, wherein the volume ratio of the silane material to the solvent is 1:20-1:100.
[0129] In some embodiments, the silane material may include a fluorosilane material or a silane coupling agent. Taking the fluorosilane material as an example, it includes at least one of perfluorodecyl trimethoxysilane, perfluorooctyl triethoxysilane, perfluorododecyl trimethoxysilane and trifluoropropyl methyl silane. Taking the silane coupling agent as an example, it includes at least one of γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, sulfur-containing silane coupling agent, epoxy silane coupling agent and γ-urea propyl triethoxysilane. The above-mentioned silane material has low solubility in water, so the modified solution may also include an organic solvent, specifically an ester solvent and / or an alcohol solvent. The organic solvent can increase the solubility of the silane material and can inhibit the hydrolysis rate of the modified solution including the silane material and water to a certain extent. Specifically, the ester solvent includes ethyl acetate, and the alcohol solvent includes ethanol, ethanol and butanediol.
[0130] According to the present application, the step of modifying the composite metal oxide layer with a silane-type material includes allowing a modification solution including a silane-type material and water to contact and react with at least a portion of the surface of the composite metal oxide layer to form a modified layer on the composite metal oxide layer, thereby obtaining a composite metal oxide layer modified with a silane-type material as the composite metal oxide layer of the present application.
[0131] In the embodiment of the present application, the silane material can act on at least part of the surface of the composite metal oxide layer, wherein at least part of the surface can be the active surface of the product when in use. Taking the cookware as an example, the composite metal oxide layer is formed on the entire inner surface of the cookware, and the active surface can be the area on the composite metal oxide layer corresponding to the bottom wall area of the inner surface of the cookware. Of course, at least part of the surface can also be the entire surface of the product, for example, the entire outer surface of the composite metal oxide layer.
[0132] In an embodiment of the present application, the composite metal oxide layer (modified layer) modified by a silane material is a product obtained by reacting a hydrolyzate of a silane material with a composite metal oxide layer. The modified solution may at least contact at least a portion of the outer surface of the composite metal oxide layer, thereby obtaining a modified layer formed on the surface of the composite metal oxide layer. Of course, the modified solution may also enter the surface pores of the composite metal oxide layer to contact the inner wall surface of the corresponding pores, thereby forming a modified layer on the inner wall surface of the pores. Here, the surface pores refer to the pores / holes existing in the region of a certain depth from the outer surface of the composite metal oxide layer to the inner surface. In this case, the modified layer may not only exist on the outer surface of the composite metal oxide layer, but may also exist on the inner wall surface of the surface pores of the composite metal oxide layer.
[0133] According to the present application, the composite metal oxide layer and the modified layer thereon are bonded at least by chemical bonds, and have a certain bonding strength, thus ensuring that they are not easy to fall off during use.
[0134] According to the present application, a modified solution including a silane material is brought into contact with and reacted with a composite metal oxide layer, thereby obtaining a non-stick coating having a modified layer on at least the surface. The contact may refer to immersing the composite metal oxide layer in a modified solution including a silane material and water. Specifically, the surface of the composite metal oxide layer has silanol groups. During the contact process, first, the silane material can be hydrolyzed to generate a siloxane material, and then the generated siloxane material undergoes a dehydration reaction with the silanol groups on the surface of the composite metal oxide layer to form a modified layer, thereby obtaining a composite metal oxide layer modified by a silane material. The composite metal oxide layer modified by a silane material has extremely strong hydrophobicity, low surface energy, and a large contact angle, so that the initial non-stickiness of the composite metal oxide layer is better.
[0135] According to the present application, the modified solution including the silane material can be stably hydrolyzed in an acidic environment. In an exemplary embodiment, the pH value of the modified solution of the silane material is not greater than 7, and dilute hydrochloric acid can be added to the modified solution to obtain a modified solution with a predetermined pH value.
[0136] According to the present application, the hydrolysis of the silane material can be ensured by heating. Specifically, an ultrasonic method can be used to make at least part of the surface of the composite metal oxide layer contact with the modified solution containing the silane material under heating conditions, for example, ultrasonic vibration is used, and the vibration frequency is set to 20KHz-50KHz, and the temperature is heated to 50°C-80°C for 5min-8min.
[0137] (2) Filling the composite metal oxide layer with oil molecules
[0138] According to the present application, in order to further optimize the non-stick property, oil molecules or oils can be filled in the factory, so that the non-stick property of the composite metal oxide layer can be further optimized, and in the subsequent use process, the oil in the cooking process can also be replenished in the three-dimensional pore structure to form a continuous and stable oil film to exert the non-stick property. Below, the filling of oil molecules will be taken as an example to describe an embodiment according to one aspect of the present application.
[0139] According to the present application, the oil molecules can be selected from at least one of methyl oil molecules, dimethyl oil molecules, hydroxyl oil molecules, hydrogen-containing oil molecules and polyether modified oil molecules. The above oil molecules have specific viscosity and surface tension, and are easier to enter the three-dimensional pore structure of the composite metal oxide layer. In this case, the oil molecules are adsorbed or bonded to the three-dimensional pore structure of the composite metal oxide layer. In addition, by weight percentage, the oil molecules include 20%-30% low molecular weight oil molecules, 40%-60% medium molecular weight oil molecules, and 20%-30% high molecular weight oil molecules, wherein the molecular weight of the low molecular weight oil molecules is between 500-1000, the molecular weight of the medium molecular weight oil molecules is between 3000-6000, and the molecular weight of the high molecular weight oil molecules is between 12000-30000.
[0140] In these embodiments, the large molecular weight oil molecules are more firmly bonded to the structure formed by the accumulation of the base material, and the release speed is slower, the small molecular weight oil molecules have better free mobility and thus have better non-stickiness, and the medium molecular weight oil molecules have both free mobility and strong bonding. Therefore, by combining low molecular weight oil molecules, medium molecular weight oil molecules and high molecular weight oil molecules, on the one hand, the possibility of oil molecules entering the composite metal oxide layer is further increased, and on the other hand, oil molecules with different binding forces can be continuously released at various stages of use to exert a better non-stick effect. As an example, the binding force between the oil molecules and the composite metal oxide layer is approximately 10KPa-25KPa. Such a binding force can ensure the continuous release of the oil molecules and avoid the oil molecules from being released too early or not being released.
[0141] According to the present application, oil molecules are used to impregnate the composite metal oxide layer, thereby obtaining non-stick cookware in which the oil molecules are combined in the pore structure of the composite metal oxide layer. As an example, in the coating of the non-stick cookware, the weight of the oil molecules accounts for 5%-10% of the total weight of the coating of the non-stick cookware, taking the total weight of the coating of the non-stick cookware as 100%, and the remainder is the composite metal oxide layer formed by the microspheres. As an example, the time for the oil molecules to impregnate the composite metal oxide layer can be 15min-30min, and the temperature can be 80℃-120℃, and then the excess oil molecules on the surface are wiped dry, and then dried at a temperature of 280℃-340℃ and a time of 3min-6min.
[0142] The present application will be described in detail below in conjunction with specific embodiments, but the protection scope of the present application is not limited to the embodiments.
[0143] Example 1
[0144] The cookware according to Example 1 was manufactured by the following method.
[0145] Step S10, preparing a cookware substrate. Specifically, the step of preparing the cookware substrate includes deep drawing a stainless steel sheet, alkali washing and degreasing the surface, drying, and sandblasting to remove surface defects and scale of the stainless steel, thereby obtaining a cookware substrate with a thickness of 1.5 cm and a surface roughness of 4 microns. Here, the cookware substrate has a bottom plane structure and a wall structure, and the bottom plane structure is conducive to the stability of placement on a countertop and is suitable for use on an induction cooker, and a subsequent composite metal oxide layer is formed at least on the bottom plane structure.
[0146] Step S20, prepare a composite metal oxide with an average particle size of 50 microns. Wherein, a base material with an average particle size of 0.05 microns to 0.1 microns (the base material is a mixture formed by titanium oxide and ferrosoferric oxide in a weight ratio of 1:1) and polyvinyl alcohol are mixed in a weight ratio of 60:40 to form a mixed slurry, and the mixed slurry is spray-dried to obtain non-stick particles, and then the obtained non-stick particles are heated to 600°C at a heating rate of 18°C / min, and the heat preservation time is 7h, and finally, the temperature is increased to 1230°C at a heating rate of 70°C / min, and the temperature is kept for 18h for sintering. During the sintering process, the base material is slightly melted, and each oxide undergoes a chemical reaction, thereby forming a composite metal oxide with an amorphous structure as a composite metal oxide according to the present application.
[0147] Step S30, spraying with composite metal oxides.
[0148] The outer surface of the cookware substrate is placed in a circulating cooling air gas environment, wherein the temperature of the cooling gas is 5° C. The composite metal oxide is loaded into a powder feeder, and the spraying parameters of the plasma spraying are set as follows: powder feeding speed 13 g / min, spraying distance 160 mm, arc current 400 A, voltage 60 V, hydrogen pressure 0.7 MPa, hydrogen flow 250 L / h, argon pressure 1.2 MPa, argon flow 1500 L / h, workpiece linear speed 30 m / min. The composite metal oxide powder is formed on the inner surface of the cookware substrate by plasma spraying to obtain a composite metal oxide layer with a thickness of 65 μm, thereby completing the manufacture of the cookware of Example 1.
[0149] Example 2
[0150] The cookware of Example 2 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide and ferrosoferric oxide in a weight ratio of 39:13) is used to replace the base material of Example 1.
[0151] Example 3
[0152] The cookware of Example 3 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide and ferrosoferric oxide in a weight ratio of 13:39) is used to replace the base material of Example 1.
[0153] Example 4
[0154] The cookware of Example 4 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide and potassium oxide in a weight ratio of 26:26:1.5) is used to replace the base material of Example 1.
[0155] Example 5
[0156] The cookware of Example 5 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide and sodium oxide in a weight ratio of 26:26:1.5) is used to replace the base material of Example 1.
[0157] Example 6
[0158] The cookware of Example 6 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide and calcium oxide in a weight ratio of 26:26:1.5) is used to replace the base material of Example 1.
[0159] Example 7
[0160] The cookware of Example 7 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide and magnesium oxide in a weight ratio of 26:26:1.5) is used to replace the base material of Example 1.
[0161] Example 8
[0162] The cookware of Example 8 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide, sodium oxide, and calcium oxide in a weight ratio of 26:26:1.5:1.5) is used to replace the base material of Example 1.
[0163] Example 9
[0164] The cookware of Example 9 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide, sodium oxide, and magnesium oxide in a weight ratio of 26:26:1.5:1.5) is used to replace the base material of Example 1.
[0165] Example 10
[0166] The cookware of Example 10 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide, potassium oxide, and calcium oxide in a weight ratio of 26:26:1.5:1.5) is used to replace the base material of Example 1.
[0167] Embodiment 11
[0168] The cookware of Example 11 is manufactured by the same method as Example 1, except that in step S20, a different base material (the base material of this embodiment is a mixture of titanium oxide, ferrosoferric oxide, potassium oxide, and magnesium oxide in a weight ratio of 26:26:1.5:1.5) is used to replace the base material of Example 1.
[0169] Example 12
[0170] The cookware of Example 12 is manufactured in the same manner as in Example 1, except that after step S30, a step of coating silicone oil molecules on the composite metal oxide layer and curing the layer (curing time is 5 minutes, curing temperature is 350° C.) is added.
[0171] Example 13
[0172] The cookware of Example 13 is manufactured by the same method as in Example 1, except that after step S30, a silane material is grafted onto the composite metal oxide layer of Example 1 (specifically, an ultrasonic method is used to make at least a portion of the surface of the initial composite metal oxide layer contact with a modified solution containing N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane under ultrasonic conditions, and the vibration frequency is set to 30 kHz, heated to 60°C, and the time is 6 minutes).
[0173] Embodiment 14
[0174] The cookware of Example 14 is manufactured by the same method as Example 8, except that after step S30, a silane-based material is grafted onto the composite metal oxide layer of Example 8 (specifically, an ultrasonic method is used to make at least a portion of the surface of the initial composite metal oxide layer contact with a modified solution containing N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane under ultrasonic conditions, and the vibration frequency is set to 30 KHz, heated to 60°C, and the time is 6 minutes).
[0175] Embodiment 15
[0176] The cookware of Example 15 is manufactured by the same method as in Example 1, except that after step S30, a silane-based material is grafted onto the composite metal oxide layer of Example 1 (specifically, an ultrasonic method is used to make at least a portion of the surface of the initial composite metal oxide layer contact with a modified solution containing perfluorodecyltrimethoxysilane under ultrasonic conditions, and the vibration frequency is set to 30 kHz, heated to 60°C, and the time is 6 minutes).
[0177] Example 16
[0178] The cookware of Example 16 is manufactured by the same method as Example 8, except that after step S30, a silane-based material is grafted onto the composite metal oxide layer of Example 8 (specifically, an ultrasonic method is used to make at least a portion of the surface of the initial composite metal oxide layer contact with a modified solution containing perfluorodecyltrimethoxysilane under ultrasonic conditions, and the vibration frequency is set to 30 kHz, heated to 60°C, and the time is 6 minutes).
[0179] Embodiment 17
[0180] The cookware of Example 17 is manufactured in the same manner as in Example 1, except that before step S20, a transition layer with a thickness of 40 μm is formed on the cookware substrate using titanium alloy.
[0181] Embodiment 18
[0182] The cookware of Example 18 is manufactured in the same manner as in Example 1, except that in step S30, the outer surface of the cookware base is placed at room temperature instead of being placed in an environment of circulating cooling air.
[0183] Embodiment 19
[0184] The cookware of Example 19 is manufactured by the same method as Example 1, except that in step S20, the composite metal oxide of Example 1 is sintered (sintering temperature is 1400°C, sintering time is 4h), and then cooled at a cooling rate of 80°C / s to replace the composite metal oxide of Example 1.
[0185] Embodiment 20
[0186] The cookware of Example 20 is manufactured in the same manner as in Example 8, except that in step S20, the composite metal oxide of Example 8 is sintered (the sintering temperature is 1400°C, and the sintering time is 4h), and then cooled at a cooling rate of 80°C / s to replace the composite metal oxide of Example 8.
[0187] Embodiment 21
[0188] The cookware of Example 21 is manufactured by the same method as Example 1, except that in step S10, a concave-convex structure (the vertical distance h between the highest point of the convexity of the concave-convex structure and the lowest point of the concave-convex structure is 0.1 mm, the top width w1 of the convexity is 2 mm, and the bottom width w2 of the convexity is 4 mm) is provided on the cookware base to replace the cookware base of Example 1.
[0189] Embodiment 22
[0190] The cookware of Example 22 is manufactured by the same method as Example 8, except that in step S10, a concave-convex structure (the vertical distance h between the highest point of the convexity of the concave-convex structure and the lowest point of the concave-convex structure is 0.1 mm, the top width w1 of the convexity is 2 mm, and the bottom width w2 of the convexity is 4 mm) is provided on the cookware base to replace the cookware base of Example 8.
[0191] Comparative Example 1
[0192] The cookware of comparative example 1 is manufactured by the same method as in example 1, except that in step S20, different materials (the materials in this comparative example are a mixture of 21.06% silicon dioxide, 1.32% aluminum oxide, 0.44% potassium oxide, 0.27% sodium oxide, 3.71% calcium oxide, 1.19% magnesium oxide, 0.45% titanium oxide, 69.59% iron oxide and the remainder impurities) are used to replace the composite metal oxide of example 1.
[0193] Comparative Example 2
[0194] The cookware of comparative example 2 is manufactured by the same method as in example 1, except that in step S20, different materials (the materials in this comparative example are a mixture of 30% silicon dioxide, 1.32% aluminum oxide, 0.44% potassium oxide, 0.27% sodium oxide, 3.71% calcium oxide, 1.19% magnesium oxide, 0.45% titanium oxide, 50% iron oxide and the remainder impurities) are used to replace the composite metal oxide of example 1.
[0195] Comparative Example 3
[0196] The cookware of Comparative Example 3 is manufactured by the same method as Example 1, except that in step S20, a different amorphous material (the materials in this comparative example are 45wt% titanium dioxide, 45wt% iron oxide + ferrous oxide, 5wt% calcium oxide + magnesium oxide, and the remainder phosphorus, carbon and silicon) is used to replace the composite metal oxide of Example 1.
[0197] Comparative Example 4
[0198] The cookware of Comparative Example 4 is manufactured by the same method as that of Example 1, except that in step S20, a different material (the material of this comparative example is aluminum magnesium ferrous titanate) is used to replace the composite metal oxide of Example 1.
[0199] Comparative Example 5
[0200] The cookware of Comparative Example 5 was manufactured in the same manner as in Example 1, except that in step S20, the material obtained by sintering the non-stick particles at a temperature of 200° C. was used instead of the composite metal oxide in Example 1.
[0201] Test methods, evaluation criteria, and test results
[0202] 1. The amorphization degree of the composite metal oxides in Examples 1 to 11, 19 and 20 and the materials in Comparative Examples 1 to 5 was tested, and the test results are shown in Table 1 below.
[0203] Amorphous degree test method: XRD test is used and the conventional full spectrum fitting method is used for analysis and calculation to obtain the amorphous degree of the sample. The steps of the conventional full spectrum fitting method are as follows: First, find a crystalline phase with the same chemical structure as the amorphous phase, assuming that the amorphous phase is a tiny grain of this crystalline phase, and this crystalline phase can be used to establish a model of the peak position and intensity of the amorphous phase; secondly, fit the spectrum of the pure amorphous phase to determine the grain size and micro-strain; finally, fix the grain size and micro-strain, include this phase in the traditional Rietveld quantitative calculation, and the volume proportion of the amorphous phase of the corresponding material (that is, the degree of amorphization) can be obtained.
[0204] Table 1 Test results
[0205]
[0206]
[0207] It can be seen from Table 1 that the composite metal oxide in the embodiment of the present application is a composite metal oxide having a certain volume percentage of an amorphous phase.
[0208] 2. The coatings of the cookware obtained in the above-mentioned Examples 1-20 and Comparative Examples 1-5 were subjected to performance tests and recorded in the following Table 2. The specific performance test method is as follows:
[0209] Test methods and evaluation criteria
[0210] 1. Amorphous degree test method: refer to the amorphous degree test method in composite metal oxides.
[0211] 2. Initial non-stickiness test method and evaluation standard: GB / T32095.2-2015 fried egg non-stickiness test method. This method is an initial non-stickiness test, which is divided into levels Ⅰ, Ⅱ, and Ⅲ. Level Ⅰ has the best non-stickiness and level Ⅲ has the worst non-stickiness.
[0212] 3. Long-term non-stick test method and evaluation standard: The long-term non-stick test method in GB / T32388-2015 is measured in times. The higher the number, the longer the life. The non-stick result is evaluated every 500 times, and the number of times when it is used to level III is recorded.
[0213] 4. Hardness test method and evaluation criteria: The Vickers hardness test method is used to test the Vickers hardness of the obtained cookware coating, where the hardness value unit is HV. The larger the measured hardness value, the harder the sample, the stronger the layer's resistance to abrasion by shovels and food materials, and the less likely it is to be worn. However, if it is too hard, it may be easy to crack. Generally speaking, the hardness of the desired layer is not less than 200HV and not more than 600HV.
[0214] 5. Surface energy test and evaluation criteria: At a temperature of 20°C, use a SINDINSDC-200SH contact angle meter to measure the contact angles of water and ethylene glycol on the sample surface according to the angle measurement method, and use the OWRK method to calculate the surface energy of the sample. Here, the sample is the coating corresponding to the embodiment and the comparative example, and the measured surface energy value of the sample is expected to be no more than 100 dynes.
[0215] Table 2 Test results
[0216]
[0217]
[0218] As can be seen from Table 2, the composite metal oxide layer obtained in the present application has excellent initial non-stickiness and lasting non-stickiness, and has a suitable hardness, which can avoid cracking caused by excessive hardness of the coating. By sealing the coating formed by the thermal spraying process, a lower surface energy than the fluorine coating can be obtained to ensure initial non-stickiness. By controlling the spraying process (i.e., placing the outer surface of the pot under a cooling gas environment in the plasma spraying process), the amorphization degree of the composite metal oxide layer can be increased to a certain extent, so that the surface energy is relatively low, thereby ensuring good lasting non-stick performance.
[0219] Although the present invention has been specifically shown and described with reference to exemplary embodiments of the present invention, it will be understood by those skilled in the art that various changes in form and detail may be made herein without departing from the spirit and scope of the present invention as defined by the claims and their equivalents. The embodiments should be considered in a descriptive sense only and not for the purpose of limitation. Therefore, the scope of the present invention is not limited by the specific embodiments of the present invention, but by the claims, and all differences within the scope will be interpreted as included in the present invention.
Claims
1. A non-stick cooker, characterized in that: The non-stick cookware includes a substrate and a composite metal oxide layer with an amorphous structure arranged on the substrate, the surface of the composite metal oxide layer has a concave-convex structure, and a low surface energy material is formed at least in the concave part of the concave-convex structure, wherein the metal elements in the composite metal oxide layer include iron elements of different valence states and titanium elements of different valence states.
2. The non-stick cooker according to claim 1, characterized in that: The iron elements of different valence states include +2 and +3, and the titanium elements of different valence states include at least two of +2, +3 and +4.
3. The non-stick cookware according to claim 1, characterized in that: The composite metal oxide layer also contains carbonized products of the binder dispersed therein.
4. The non-stick cooker according to claim 3, characterized in that: The weight ratio of the carbonized product of the binder to the composite metal oxide layer is (0.4-3.5):(96.5-99.6).
5. The non-stick cookware according to claim 1, characterized in that: The porosity of the composite metal oxide layer is 5%-30%, and the pore size is 500 nanometers-4 micrometers.
6. The non-stick cooker according to claim 1, characterized in that: The composite metal oxide layer is a material in which the volume proportion of the amorphous phase is in the range of 30%-70%.
7. The non-stick cooker according to claim 1, characterized in that: The low surface energy material includes at least one of silane materials, oil molecules, fluorine coatings and ceramic coatings.
8. A method for manufacturing non-stick cookware, characterized in that: The manufacturing method of the non-stick cooker comprises: forming a mixed slurry including a binder and a base material, wherein the base material includes titanium oxide and ferrosoferric oxide; spray drying the mixed slurry to obtain non-stick particles; Sintering the non-stick particles to slightly melt the base material in the non-stick particles, thereby obtaining a composite metal oxide including iron elements of different valence states and titanium elements of different valence states and having an amorphous structure; Spraying the composite metal oxide on the substrate to form a composite metal oxide layer having a concave-convex structure on the substrate; A low surface energy material is formed at least at the concave part of the concave-convex structure, thereby manufacturing the non-stick cookware.
9. The method for manufacturing non-stick cookware according to claim 8, characterized in that: The weight ratio of the base material to the binder is (52-70):(30-48); and / or the weight ratio of titanium oxide to ferrosoferric oxide is (13-39):(13-39); and / or the particle size of the base material is 0.05 microns to 5 microns.
10. The method for manufacturing non-stick cookware according to claim 8, characterized in that: The binder includes an alcohol binder and / or a cellulose binder.
11. The method for manufacturing non-stick cookware according to claim 10, characterized in that: The cellulose binder includes at least one of hydroxymethyl cellulose binders, hydroxyethyl cellulose binders and hydroxypropyl cellulose binders; and / or the alcohol binder includes at least one of polyvinyl alcohol binders, polypropylene alcohol binders and higher alcohol binders containing more than six carbon atoms.
12. The method for manufacturing non-stick cookware according to claim 8, characterized in that: The sintering step comprises: The non-stick particles are heated to 500-650°C at a heating rate of 15-20°C / min, kept warm for 6-8h, and then heated to 1200-1250°C at a heating rate of 55-100°C / min, and kept warm for 12-24h.